2012
DOI: 10.1007/s00405-012-2199-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of packing or transseptal suture on polysomnographic parameters in septoplasty

Abstract: Our objective is to examine the effects of using nasal packing or transseptal suture in septoplasty in young patients, specifically on the polysomnographic parameters in the post-operative period. A total of 43 patients who had undergone septoplasty surgery after a diagnosis of septum deviation were included in the study. Packing was inserted in 23 patients, and transseptal suture was performed in the other 20 patients. A polysomnography test was performed on the patients on the first day after surgery and dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
2
8
0
1
Order By: Relevance
“…These results were consistent with the study by Said et al [ 9 ]. There were significant sleep disturbances and dysphagia on the first postoperative day in the packing group compared to the suturing group, consistent with the results of Turhan et al [ 13 ] and Korkut et al [ 14 ], respectively. If a patient swallows with the nasal passages blocked (Toynbee maneuver), air cannot pass anteriorly and is insufflated into the middle ear.…”
Section: Discussionsupporting
confidence: 90%
“…These results were consistent with the study by Said et al [ 9 ]. There were significant sleep disturbances and dysphagia on the first postoperative day in the packing group compared to the suturing group, consistent with the results of Turhan et al [ 13 ] and Korkut et al [ 14 ], respectively. If a patient swallows with the nasal passages blocked (Toynbee maneuver), air cannot pass anteriorly and is insufflated into the middle ear.…”
Section: Discussionsupporting
confidence: 90%
“…This procedure has been proposed to minimize postoperative complications such as hemorrhage, formation of synechiae, and septal hematoma [3]. However, currently, there are no general standards concerning the indications for intranasal packing, duration of packing, or the type of material used [4], and a large number of complications have been reported using this procedure [5].…”
Section: Introductionmentioning
confidence: 99%
“…[22] Previous studies have shown a wide variation in the prevalence of OSAS, which, in general, is high. [23,24] Our findings showed that in multivariate analysis, the presence of OSAS reached statistical significance in the assessment of difficult airway, which emphasizes the importance of taking a detailed history and examining the patient for OSAS during pre-anesthetic check-up in predicting difficult airway.…”
Section: Discussionmentioning
confidence: 61%